Peningkatan Pengetahuan dan Ketrampilan Ibu Menyusui Dalam Pemberian Terapy Komplementer Massage Endorphin dan Pijat Laktasi di Debong Lor - Evi Zulfiana; Ulfatul Latifah; Mutiarawati Mutiarawati; Nora Rahmanindar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Breastfeeding is a natural process that is not easy to do. Exclusive breastfeeding coverage can not be separated from the problems that occur in the breastfeeding process including the false belief that breast milk comes out a little or breast milk is insufficient for the baby. This condition is caused by several factors including food and drinks consumed by the mother, the psychological or emotional condition of the mother, abnormal breast shape. New methods introduced to prevent and overcome this problem include endorphin massage and Lactation massage massage massage technique performed on the head or neck, back, spine, and breast areas that aim to stimulate the hormone prolactin and oxytocin. The purpose of this devotion is to increase the knowledge and skills of nursing mothers in doing endorphin massage and lactation massage. The method is to provide training starting with the material of the correct way of breastfeeding. The results of training that has been given to breastfeeding mothers who follow posyandu already know and skill in practicing endorphine massage and lactation massage